An Overview of Microplastics in the Marine Ecosystem of North Maluku - Badrun Ahmad; Muhammad Taufiq Y.S; Sudirman Hi Umar (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
North Maluku has been the site of microplastic study for some years. The goal of this paper is to revisit the earlier analysis. The intent is to be a quick guide for scholars studying microplastics in North Maluku. Additionally, this article’s goal is to quantitatively analyse some of the findings from the research that has been done. The terms "Microplastics in the North Maluku Sea" were entered into the search engines Google Scholar and Science Direct to conduct journal and research searches. Previous studies on microplastics on Mare Island looked at sediments in the island’s waters and the levels of microplastics in various kinds of sea cucumbers. A total of 272 microplastic fragments were discovered in sea cucumbers. At the same time, two stations were doing a study on deposits. Microplastics weighing between 17,000 and 37,000 particles/kg of dry sediment were discovered at the first station in Maregam. 13,839-30,666 particles/kg of silt were discovered in Marekofo. According to research conducted on the island of Ternate, skipjack tuna contains up to 948 microplastic particles that were collected from 16 market fish samples. According to studies on other fish species like Epinephelus Fuscogutattus, E. coioides, and E. Suillus, the digestive tract of fish contains 594 microplastic particles.